PREDICTORS OF CHARACTER STRENGTHS AMONG YOUNG ADULTS AND ADULTS IN BANDUNG - Polii, Evi Ema Victoria; Vivekananda, Ni Luh Ayu (JIV-Jurnal Ilmiah Visi, 2023)
This study aims to measure the contribution of traits and productive parenting patterns as predictors of character strengths. Features were assumed as a natural or an innate factor in individuals, while effective parenting patterns were considered a nurture or an external factor. In this study, the trait concept is studied using the theory of Five-Factor Personality from Costa and McRae; the productive parenting pattern is studied using Baumrind’s approach, and the idea of character strengths is explored using the theory proposed by Peterson and Seligman. The validity and reliability of all questionnaires are examined by construct validity and internal consistency. Respondents were 247 individuals with a young adult to the adult developmental range. The result of regression analysis shows that traits and productive parenting patterns significantly contributed to establishing all character strengths with the value of R2 from 0.226 to 0.562. This finding concludes that character strengths will be well developed in individuals if the innate factor (traits) are optimized with productive parenting (with acceptance and warmth and clear and consistent rules from the parents).